Insulin Regulates Glucagon-Like Peptide-1 Secretion from the Enteroendocrine L Cell - Lim, Gareth E. (Endocrinology, 2009)
Insulin resistance and type 2 diabetes mellitus are associated with impaired postprandial secretion of glucagon-like peptide-1 (GLP-1), a potent insulinotropic hormone. The direct effects of insulin and insulin resistance on the L cell are unknown. We therefore hypothesized that the L cell is responsive to insulin and that insulin resistance impairs GLP-1 secretion. The effects of insulin and insulin resistance were examined in well-characterized L cell models: murine GLUTag, human NCI-H716, and fetal rat intestinal cells. MKR mice, a model of chronic hyperinsulinemia, were used to assess the function of the L cell in vivo. In all cells, insulin activated the phosphatidylinositol 3 kinase-Akt and MAPK kinase (MEK)-ERK1/2 pathways and stimulated GLP-1 secretion by up to 275 ± 58%. Insulin resistance was induced by 24 h pretreatment with 10(−7) m insulin, causing a marked reduction in activation of Akt and ERK1/2. Furthermore, both insulin-induced GLP-1 release and secretion in response to glucose-dependent insulinotropic peptide and phorbol-12-myristate-13-acetate were significantly attenuated. Whereas inhibition of phosphatidylinositol 3 kinase with LY294002 potentiated insulin-induced GLP-1 release, secretion was abrogated by inhibiting the MEK-ERK1/2 pathway with PD98059 or by overexpression of a kinase-dead MEK1-ERK2 fusion protein. Compared with controls, MKR mice were insulin resistant and displayed significantly higher fasting plasma insulin levels. Furthermore, they had significantly higher basal GLP-1 levels but displayed impaired GLP-1 secretion after an oral glucose challenge. These findings indicate that the intestinal L cell is responsive to insulin and that insulin resistance in vitro and in vivo is associated with impaired GLP-1 secretion.